Numerical Approach of Single-Junction InGaN Solar Cell Affected by Carrier Lifetime and Temperature - Parajuli, D.; Bhandari, Viplav; K.C., Devendra; Thapaliya, Ajita; Subedi, Amrit; Dhakal, Amrit; Dangi, Sandip; Koirala, Rabina; Bhatta, Manish (Pragya Darshan प्रज्ञा दर्शन, 2023)
The PC1D simulation aand origin software were successfully used for the study of Carrier Lifetime and Temperature effect on InGaN Single-Junction Solar Cell. For the simulation, the total device area was 100 cm2, dielectric constant 13.1, band gap 1.35eV, intrinsic constant is 1×1010 cm-3, doping concentration is 1×1017 cm-3, electron number and hole number 1000 and 170 respectively, and the refractive index was 3.58. The optimized temperature and bulk recombination were 25°C and 1000μs respectively along with the efficiency of 18.258 % for both n and p - InGaN solar cell. Several graphs were plotted under the following conditions: a) bulk recombination time of p-InGaN and temperature are kept constant at 1000 μs and 25°C, the variation of bulk recombination time of n - type InGaN solar cell with base current and voltage, maximum current and voltage, and efficiency and maximum power were studied. b) bulk recombination time of n-InGaN and temperature are kept constant at 1000 μs and 25°C, the variation of bulk recombination time of p - type InGaN solar cell with base current and voltage, maximum current and voltage, and efficiency and maximum power were studied.